In-hospital outcomes of patients with non-iatrogenic civilian vascular trauma - Meyer, Alexander; Hübner, Viola; Lang, Werner; Almási-Sperling, Veronika; Rother, Ulrich (Vasa-Journal of Vascular Diseases, 2020)
Background: Morbidity, lesion pattern, management and short-term outcomes of civilian vascular trauma are rarely evaluated. Therefore, analysis of in hospital results in patients with nor-iatrogenic vascular trauma in a tertiary referral hospital was performed. Patients and methods: Retrospective evaluation of patients with vascular trauma from 2007-2017 was done. 48 patients (34 male, 14 females, mean age 56 years) were included. Excluded were patients with iatrogenic vascular complications. Major cause of vascular trauma were traffic accidents in 43.8 %, fall from great heights in 27.1 %, sport and home related injuries in 16.8 %, suicidal injuries in 4.2 % and gunshot wounds in 2.1 % (other 6.3 %). 60.4 % of patients presented with blunt, 39.6 % of patients with penetrating vascular trauma. More than half of the cases included polytraumatized patients (544 %). Results: Most commonly affected were the popliteal (25.0 %) and the axillar artery (18.8 %). Aortic injuries were present in 14.6 % of cases, whereas the femoral and subclavian artery were involved in 12.6 % and 10.4 %. Vascular reconstruction was performed by interposition graft in 45.9 %, direct suture in 18.8 %, patchplasty in 10.4 %, ligation in 124 %, and implantation of stentgraft in 12.5 %. Postoperative complication rate was 54.2 %. Rate of in-hospital major amputation was 14.6 % and in-hospital mortality was 14.6 % as well. Comparison between blunt and penetrating trauma as to postoperative complication (p = 0.322), blood transfusion (p = 0.452) and amputation (p = 0.304) showed no significant differences, whereas lethality in blunt trauma was 20.6 % vs. 5.2 % in penetrating trauma. Injury severity score (ISS) was significantly elevated for blunt trauma patients (mean ISS Score blunt 32 vs 21 penetrating, p = 0.043). Conclusions: The majority of vascular lesions is caused by blunt trauma. Blunt lesions do also show a severe injury pattern, compared to penetrating trauma, and the complication rate remains high. However, by means of vascular reconstruction, limb salvage is feasible in a high percentage of cases.
CRIS-Team WoS Importer:2020-05-15